2015
DOI: 10.1002/alr.21544
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal extramedullary plasmacytoma: a population‐based incidence and survival analysis

Abstract: This study analyzed the largest cohort of SN-EMP patients to date. There was no statistically significant survival advantage found for any 1 particular treatment modality over other treatment modalities in both SN-EMP and other HN-EMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
3
23
0
1
Order By: Relevance
“…This finding supports previously reported results, which suggested that SBP is frequently observed in marrow-containing bones, specifically vertebrae [19]. In addition, and in accordance with the findings reported by Patel et al, we found when analyzing our sample that the upper airway tract, including the sinuses, which have extensive lymphatic supply, was the most commonly involved EMP site [20]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding supports previously reported results, which suggested that SBP is frequently observed in marrow-containing bones, specifically vertebrae [19]. In addition, and in accordance with the findings reported by Patel et al, we found when analyzing our sample that the upper airway tract, including the sinuses, which have extensive lymphatic supply, was the most commonly involved EMP site [20]. …”
Section: Discussionsupporting
confidence: 93%
“…Our findings concur with this conclusion, with a male-to-female ratio of 1.6:1 [4, 20]. In existing studies focusing primarily on SBP, the male-to-female ratio was in the range of 1.5–2.4 [5, 6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This dataset encompasses over 30 years of patient information. However, as with other large databases, the inability to access primary patient data may affect the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 4). Patel et al 58 identified 778 patients with EMP in the head and neck region, 137 of them reportedly have plasmacytoma in the nasopharynx. D'Aguillo et al 59 reported 176 cases of sinonasal extramedullary plasmacytoma, of which 36 cases were associated with the nasopharynx (Table 6).…”
mentioning
confidence: 99%